Hijrat-i Afg̲ẖānistān : tahrīk-i Ḵẖilāfat kī ek dildoz dāstān : ek mard-i ḥurr Ḥāji Faiz̤ Muḥammad Ḵẖān Ṣāḥib kī sarguzasht - Shāh, Sayyid Darbār ʻAlī (Tāj Kampanī, 1977)
On the role played by Faiz Muhammad Khan, d. 1975, a Muslim political figure, who migrated to Afghanistan in 1920 during the Indian Khilafat movement.